Sastravid - Westerhoff, J (University of Oxford, 2018)
Śāstravid (http://sastravid.theology.ox.ac.uk/index.php) is an ERC-funded web-based electronic research tool for the study of Indian philosophy. It contains a number of Indian philosophical texts (primarily from the Buddhist Madhyamaka school), some of them in the original Sanskrit, some in historical or modern translations. The unique structure of Śāstravid represents both the explicit relationships among texts—where one is a commentary on, or a translation of, another—and their conceptual connections. A researcher can view each passage in each Śāstravid text together with related commentaries and translations, and can move directly from there to other Śāstravid texts that make related points. Researchers can also browse the concepts and texts published in the system.